ACC Sulcal Patterns and Their Modulation on Cognitive Control Efficiency Across Lifespan: A Neuroanatomical Study on Bilinguals and Monolinguals. (27th July 2018) - Del Maschio, Nicola; Sulpizio, Simone; Fedeli, Davide; Ramanujan, Keerthi; Ding, Guosheng; Weekes, Brendan S; Cachia, Arnaud; Abutalebi, Jubin
Abstract: The anterior cingulate cortex (ACC) is a key structure implicated in the regulation of cognitive control (CC). Previous studies suggest that variability in the ACC sulcal pattern—a neurodevelopmental marker unaffected by maturation or plasticity after birth—is associated with intersubject differences in CC performance. Here, we investigated whether bilingual experience modulates the effects of ACC sulcal variability on CC performance across the lifespan. Using structural MRI, we first established the distribution of the ACC sulcal patterns in a large sample of healthy individuals ( N = 270) differing on gender and ethnicity. Second, a participants' subsample ( N = 157) was selected to test whether CC performance was differentially affected by ACC sulcation in bilinguals and monolinguals across age. A prevalent leftward asymmetry unaffected by gender or ethnicity was reported. Sulcal variability in the ACC predicted CC performance differently in bilinguals and monolinguals, with a reversed pattern of structure–function relationship: asymmetrical versus symmetrical ACC sulcal patterns were associated with a performance advantage in monolinguals and a performance detriment to bilinguals and vice versa. Altogether, these findings provide novel insights on the dynamic interplay between early neurodevelopment, environmental background and cognitive efficiency across age.